State of the art report on mixture toxicity. Final report - Kortenkamp, Andreas (Brussels, 2009)
"This report details the findings of a project on mixture toxicology and ecotoxicology commissioned by the European Commission, DG Environment. It describes the scientific state of the art in the field, and gives an account of the regulatory state of the art for dealing with combined exposures in the European Union, in major competing economies, including the USA and Japan and in international bodies. The scope of this report is restricted to the toxicity of mixtures of chemicals after simultaneous exposure. The term mixture toxicity is understood as unwanted adverse effects of mixtures of chemicals. In this report, combination effect, combined effect or joint action is used synonymously with mixture toxicity. Interactions of chemical factors with physical and/or biological stressors in the environment are beyond the scope of this study. The same applies to wanted beneficial effects of mixtures, such as therapeutic effects of drug combinations."